ANALISA LETTER OF COORDINATION AGREEMENT ANTARA PANGKALAN BUN APPROACH, BANJARMASIN APPROACH DAN H.ASAN TOWER TERHADAP KESELAMATAN PENERBANGAN DI RUTE W15 LAMUD DAN PALANGKARAYA - Achmad Nuzulla Thoriq Attaufiqi; Sudrajat; R. Diyan Subismo (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Letter of Coordination (LOCA) between Pangkalan Bun Approach, Banjarmasin Approach, and H.Asan Sampit Tower is a guidance for the implementation of coordination during flight operation in Pangkalan Bun and Banjarmasin Terminal Control Area (TMA). Formulation of the problems during this research are “Does LOCA between Pangkalan Bun APP, Banjarmasin APP,dan H.Asan Sampit TWR affect aviation safety on W15 Lamud route and Palangkaraya?”, and “Does it necessary to re- discuss the current LOCA to minimize potential conflicts that may occur?”. This research aimed to analyze, investigate, and to give the best solution for the application of current LOCA in order to provide smoothness in the provision of air traffic services in Pangkalan Bun and Banjarmasin TMA as well as the requirement for obtaining Associate Degree in diploma 3 Air Traffic Controller course. The research method in this study that author uses is quantitative descriptive research. The population in this study were all air traffic Air Traffic Controller (ATC) personnel of PERUM LPPNPI Pangkalan Bun and Sampit Branch Assistant Offices and PERUM LPPNPI Banjarmasin Branch Office, the author's research sample used the entire population as a sample of 38 samples. The author's research variable is the independent variable (X) in the form of LOCA between Pangkalan Bun APP, Banjarmasin APP, and H.Asan Sampit TWR and the dependent variable (Y) in the form of aviation safety on W15 Lamud route and Palangkaraya. The results of research from field studies (observations), interviews, questionnaires, and the calculation of the Spearman correlation coefficient of 0,68 which means that there’s strong correlation between X and Y variable. Therefore, LOCA between Pangkalan Bun APP, Banjarmasin APP, and H.Asan Sampit TWR affects the aviation safety on W15 Lamud route and Palangkaraya.